2016
DOI: 10.3389/fmicb.2016.01000
|View full text |Cite
|
Sign up to set email alerts
|

KPC-3-Producing Klebsiella pneumoniae in Portugal Linked to Previously Circulating Non-CG258 Lineages and Uncommon Genetic Platforms (Tn4401d-IncFIA and Tn4401d-IncN)

Abstract: KPC-3-producing bacteria are endemic in many countries but only recently became apparent their wide distribution in different Portuguese hospitals. The aim of this study is to characterize genetic backgrounds associated with blaKPC−3 among Klebsiella pneumoniae isolates recently identified on non-hospitalized patients in Portugal. Twenty KPC-producing K. pneumoniae identified between October 2014 and November 2015 in three different community laboratories were characterized. Isolates were mainly from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 32 publications
8
57
4
1
Order By: Relevance
“…Notably, this ST11-KL105 K. pneumoniae lineage was not detected among ESBL- or carbapenemase-producers circulating in the same clinical institutions and period of time [7, 9] , indicating that the selection of ESBL or qAmpC producing K. pneumoniae occurred independently in different genetic backgrounds, or an eventual importation event of a DHA-1-producing ST11 K. pneumoniae strain. In fact, ST11-KL105 isolates producing DHA-1 have been reported in different countries, either causing infection or linked to human colonization (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this ST11-KL105 K. pneumoniae lineage was not detected among ESBL- or carbapenemase-producers circulating in the same clinical institutions and period of time [7, 9] , indicating that the selection of ESBL or qAmpC producing K. pneumoniae occurred independently in different genetic backgrounds, or an eventual importation event of a DHA-1-producing ST11 K. pneumoniae strain. In fact, ST11-KL105 isolates producing DHA-1 have been reported in different countries, either causing infection or linked to human colonization (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In Portugal, relevant epidemiological changes regarding resistance to extended-spectrum β-lactams in Enterobacteriaceae have been observed in the last decades, including: i) escalating resistance rates to third-generation cephalosporins, ii) long-term dissemination of qAmpC (mainly in K. pneumoniae ), iii) emergence and dispersal of plasmid-mediated carbapenemase resistance and iv) the shift from E. coli to K. pneumoniae as the main species associated with this problem (https://ecdc.europa.eu/en/antimicrobial-resistance/surveillance-and-disease-data/data-ecdc) [79] . ESBL-producing Enterobacteriaceae are endemic in different Portuguese clinical settings, and the widespread of main ESBL (CTX-M-15, SHV-12), and subsequently KPC-3, had been linked to the spread of particular K. pneumoniae (ST15, ST147, ST348) or E. coli clones (ST131) and plasmid types (IncR, IncF, IncHI2) [7, 9, 10] .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed and comprehensive phylogenomics studies have shown a high specificity between certain lineages and particular K-types within CG11, CG14, CG15 or CG258 7,14,15,19,20,28 . In fact, MDR Kp expansion causing hospital or community acquired infections has been driven by clonal selection, since the population is dominated by a small number of lineages exhibiting particular K-types, where phenomes of capsular switching seem to occur sporadically at least in short time-scales (this study, Kaptive database) 6,7,38,39 . In some cases, capsular recombination events involving phenotypic changes might represent important evolutionary steps with several biological consequences, as occurred with the two different ST258 clades exhibiting KL106 or KL107 K-types, that are of interest to detect 40,41 .…”
Section: Discussionmentioning
confidence: 95%
“…Multilocus sequence typing (MLST) of K. pneumoniae 1210, determined using MLST 1.8 software (23), revealed a novel ST, which was assigned the novel allelic profile ST2728 (1-1-211-1-1-1-1) by the K. pneumoniae MLST database (http:// bigsdb.web.pasteur.fr). This sequence type is a single-locus variant (SLV) of ST15 (1-1-1-1-1-1-1-1), a pandemic clone widely described in association with carbapenemases or ESBLs and sometimes involved in outbreaks (24)(25)(26). The acquired resistance genes were identified using ResFinder server v2.1 (http://cge.cbs.dtu.dk/services/ ResFinder-2.1) (27).…”
mentioning
confidence: 99%